2021
DOI: 10.7196/samj.2021.v111i9.15909
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-induced thrombocytopenia: An update for the COVID-19 era

Abstract: This open-access article is distributed under Creative Commons licence CC-BY-NC 4.0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
(126 reference statements)
0
7
0
Order By: Relevance
“…HIT is a rare complication of heparin treatment that develops due to the production of autoantibodies (immunoglobulin G) against heparin exposure, more specifically, against PF4/heparin complexes. This leads to platelet activation and initiates the coagulation cascade that results in systemic clot formation and platelet depletion, which can further complicate the COVID-19 condition [ 10 ]. The factors associated with an increased risk are extracorporeal membrane oxygenation, surgery, hemodialysis, UFH, or low molecular-weight heparin (LMWH) [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…HIT is a rare complication of heparin treatment that develops due to the production of autoantibodies (immunoglobulin G) against heparin exposure, more specifically, against PF4/heparin complexes. This leads to platelet activation and initiates the coagulation cascade that results in systemic clot formation and platelet depletion, which can further complicate the COVID-19 condition [ 10 ]. The factors associated with an increased risk are extracorporeal membrane oxygenation, surgery, hemodialysis, UFH, or low molecular-weight heparin (LMWH) [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…HIT incidence is 0.2–0.45% in the general population, which increases to 2.7% in critically ill patients [ 10 , 16 ]. Meanwhile, the exact prevalence of HIT in COVID-19 is currently unknown, and the literature is conflicting regarding this aspect [ 10 ]. Some studies have reported a low prevalence, while others have reported a high prevalence [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations